KEPADATAN POPULASI BEKICOT (Achatina fulica Rodatzi Dunker) YANG DITEMUKAN PADA KEBUN KELAPA SAWIT DI MUARO GEDANG KABUPATEN PESISIR SELATAN - Susanti, Elma - (STKIP PGRI Sumbar, 2014)
Achatina fulica are soft-bodied animals of the class that runs using a foot gastropod stomach.Achatina fulica like damp areas so that the rainy season is a season that is highly favored bysnails. Achatina fulica is a preferred food plants are leafy and soft trunked. Achatina fulica onpalm thee gardens is endangered because of human activities using pesticides to clear landcultivation of plant pests. This can cause a food source for Achatina fulica and nothing could alsodie from pesticides. This type of research is a descriptive survey research. The sampling techniquestratified purposive sampling. Sampling consisted of 3 stations with an area of 450 m2. Sampleswere taken three times during the two-week study retrieval. The results showed that the populationdensity of Achatina fulica found in palm thee gardens in Muaro Gedang South Coastal District,found that the snail population density of 0.63 ind / m2 and an area of 450 m2. Each stationAchatina fulica population density is obtained at the first station of 0.25 ind / m2, the secondstation of 0.17 ind / m2 and the third station of 0.21 ind / m2. The state of temperature and humiditysuitable for Achatina fulica habitat .